Implementation of Guided Inquiry Model Based on Visual Cartoon Media Towards Skills of Science Process and Mastery of Concepts - Saepudin, Aep (International Journal for Educational and Vocational Studies, 2020)
This research is motivated by the science process skills of students who are still low. Factors causing low science process skills are mastery of students' concepts of subject matter is still low. The purpose of this study is 1) to describe the feasibility of learning by implementing guided inquiry model based on visual cartoon media on science process skills and mastery of the concept of environmental pollution, 2) to obtain data on guided inquiry model based on visual cartoon media can improve environmental pollution science process skills, 3) to find out the implementation of guided inquiry model based on visual cartoon media can improve mastery of the concept of environmental pollution, 4) to uncover student responses by implementing guided inquiry model based on visual cartoon media on science process skills and mastery of the concept of environmental pollution. The method used in this study is a mixed method (mixed methods research design). The sampling technique using cluster random sampling was obtained by 2 classes, each of which amounted to 40 students for the experimental class and 40 students for the control class. The research instrument used was task and rubric science process skills, mastery concept essay tests, student response questionnaires to learning and observation sheets of teacher and student activities. The data analysis technique used is the normality test, homogeneity test and hypothesis test. Based on the results of the analysis of the hypothesis test shows the value of t = 4.476 with Sig. 0.001 <0.05 means that the implementation of guided inquiry model based on visual cartoon media can improve students' science process skills in the concept of environmental pollution. Based on the results of the test analysis shows the value t = 8.486 with Sig. 0.001 < 0.05 means that the implementation of the guided inquiry model based on visual cartoon media can improve the mastery of the concept of environmental pollution.